Single-molecule studies of DNA and RNA four-way junctions. (1st February 2004) - McKinney, S.A.; Tan, E.; Wilson, T.J.; Nahas, M.K.; Déclais, A.-C.; Clegg, R.M.; Lilley, D.M.J.; Ha, T.
Abstract : Branched helical junctions are common in nucleic acids. In DNA, the four-way junction (Holliday junction) is an essential intermediate in homologous recombination and is a highly dynamic structure, capable of stacking conformer transitions and branch migration. Our single-molecule fluorescence studies provide unique insight into the energy landscape of Holliday junctions by visualizing these processes directly. In the hairpin ribozyme, an RNA four-way junction is an important structural element that enhances active-site formation by several orders of magnitude. Our single-molecule studies suggest a plausible mechanism for how the junction achieves this remarkable feat; the structural dynamics of the four-way junction bring about frequent contacts between the loops that are needed to form the active site. The most definitive evidence for this is the observation of three-state folding in single-hairpin ribozymes, the intermediate state of which is populated due to the intrinsic properties of the junction.